2007
DOI: 10.1890/06-1144.1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Macrophyte Functional Group Richness on Emergent Freshwater Wetland Functions

Abstract: Most plant diversity-function studies have been conducted in terrestrial ecosystems and have focused on plant productivity and nutrient uptake/retention, with a notable lack of attention paid to belowground processes (e.g., root dynamics, decomposition, trace gas fluxes). Here we present results from a mesocosm experiment in which we assessed how the richness of emergent macrophyte functional groups influences aboveground and belowground plant growth and microbial-mediated functions related to carbon and nitro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
68
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(76 citation statements)
references
References 38 publications
7
68
1
Order By: Relevance
“…5, solid line). These data support results of experiments demonstrating no relationship (Joabsson and Christensen, 2001;Ström et al, 2005;Koelbener et al, 2010) or even negative relationship (Bouchard et al, 2007) between CH 4 emission and plant biomass of different species. Thus, the biomass of vascular plants in peatlands cannot alone be a reliable predictor of CH 4 emissions because at least the production (shown by amount of 14 C-label) and transport (total and labeled fluxes) of CH 4 were higher for a plant species with small biomass (Ström et al, 2005;Koelbener et al, 2010).…”
Section: The Fate Of Recent Photosynthates and Their Contribution To supporting
confidence: 90%
“…5, solid line). These data support results of experiments demonstrating no relationship (Joabsson and Christensen, 2001;Ström et al, 2005;Koelbener et al, 2010) or even negative relationship (Bouchard et al, 2007) between CH 4 emission and plant biomass of different species. Thus, the biomass of vascular plants in peatlands cannot alone be a reliable predictor of CH 4 emissions because at least the production (shown by amount of 14 C-label) and transport (total and labeled fluxes) of CH 4 were higher for a plant species with small biomass (Ström et al, 2005;Koelbener et al, 2010).…”
Section: The Fate Of Recent Photosynthates and Their Contribution To supporting
confidence: 90%
“…Several studies have shown an inverse relationship between plant biomass and methane emissions from wetlands, which is often attributed to increased rhizospheric oxygenation and methane consumption with increasing biomass (Strö m et al 2005, Bouchard et al 2007, KaoKniffin et al 2010, Koelbener et al 2010. Our finding that iron reduction was occurring in unamended soils while potential methane production remained barely detectable suggests that another possible explanation for this inverse relationship may be that competition from iron reducing bacteria can inhibit methane production.…”
Section: Discussionmentioning
confidence: 57%
“…Freshwater wetland ecosystems provide a number of valuable services, including biodiversity support, water quality maintenance and improvement, flood control, and carbon storage (Zedler and Kercher 2005). While there are a number of studies documenting changes in wetland biodiversity as a consequence of human activities (Findlay and Houlahan 1997, Findlay and Bourdages 2000, Houlahan and Findlay 2004, Rosas et al 2006, Schooler et al 2006, there have been fewer studies on links between changes in biodiversity and functions that support wetland services (Engelhardt and Ritchie 2001, Mahaney et al 2006, Bouchard et al 2007, Schultz et al 2011.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations